STUDENTS PERCEPTION ON THE TEACHER’S NONVERBAL COMMUNICATION AT THE SEVENTH GRADE STUDENTS OF MTSS NAGARI BINJAI PASAMAN - Septria arima (Universitas Samudra, 2020)
ABSTRACTSeptria Arima, 2315.091. Students Perception on the Teacher’s Nonverbal Communication at the Seventh Grade Students of MTsS Nagari Binjai Pasaman. A thesis, English Educational Department, State Islamic Institute Bukittinggi, Academic Year 2019/2020The research was due to several problems found in the field: the teacher did not usually used nonverbal communication in English classroom. It is indicated by the English teacher when the researcher did the preliminary research when teaching learning process in this class. Besides, the students were difficult to understand with teacher’s nonverbal communication. It is indicated when the teacher try to silent to make the students pay attention but the fact some of students still make noise and not pay attention to the teacher in this class. The research is aimed to find out students perception on the teacher’s nonverbal communication in English class of MTsS Nagari Binjai Pasaman.The research used descriptive quantitative research by using questionnaire as an instrument. The researcher used total sampling technique because the sample less one hundred. The sample of this research was VII a and VII b of MTsS Nagari Binjai Pasaman that were 66 students as sample. The data was collected by distributed a questionnaire to each others. In addition, the analyzing of the data was done by identifying researcher respond, analyzed the data and made conclusion with level rating quality. The result of the research: first students perception on teacher’s gesture with 34,09% in rating quality of good. Second, students perception on teacher’s facial expression with 36,4% in rating quality of good. Third, students perception on teacher’s eye contact with 27,7% in rating quality of moderate. Fourth, students perception on teacher’s pitch with 18,45% in rating quality of poor. Fifth, students perception on teacher’s rate with 36,9% in rating quality of good. Sixth, students perception on teacher’s pause with 36,4% in rating quality of good. Seventh, students perception on the teacher’s friendship and warmth with 31,85% in rating quality of good. It can be concluded that students tend to have good enough perception on the teacher’s nonverbal communication in English classroom at the seventh grade students of MTsS Nagari Binjai Pasaman.